KEANEKARAGAMAN ZINGIBERACEAE SEBAGAI KONTEN MATERI KEANEKARAGAMAN HAYATI DI SMA PANDEGLANG - Muhamad Nikmatullah; Suroso Mukti Leksono; Pipit Marianingsih (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2015)
This research aimed to identify the Zingiberaceae diversity in Pandeglang which can be used as learning content for biodiversity concept in Pandeglang senior high school. The method was part of a research and development. Based on exploration, there were seven species of Zingiberaceae diversity that was utilized in Pandeglang, namely Zingiber officinale, Alpinia galanga, Curcuma domestica, Curcuma aeruginosa, Kaempferia pandurata, Kaempferia galanga, Zingiber zerumbet. The contents were developed for genetic-level biodiversity, species-level biodiversity, and ecosystem-level biodiversity learning concept.